2022
DOI: 10.1093/geroni/igac071
|View full text |Cite
|
Sign up to set email alerts
|

Untapped Insight: A Longitudinal Qualitative Analysis of Older Adults’ Advice During the COVID-19 Pandemic

Abstract: Background and Objectives Due to a lifetime of experience, older adults are uniquely positioned to contribute advice and insight to others during a historical, societal crisis such as the coronavirus disease 2019 (COVID-19) pandemic. This qualitative study explores the solicited advice older adults offered their peers, family members, and communities throughout the first year of the pandemic. Research Design and Methods A sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…At the cut-off point of our search strategy, no longitudinal studies had been found. However, in December 2022 a longitudinal study conducted in the USA explored older adult’s advice given to others [ 99 ]. They found that fostering and maintaining well-being, having a positive life perspective, and being connected to others were coping strategies during the pandemic [ 100 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the cut-off point of our search strategy, no longitudinal studies had been found. However, in December 2022 a longitudinal study conducted in the USA explored older adult’s advice given to others [ 99 ]. They found that fostering and maintaining well-being, having a positive life perspective, and being connected to others were coping strategies during the pandemic [ 100 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, older adults who were already isolated may have been at increased risk for the exacerbating effects of mental health issues, and, as suggested by our study, had less ability to supplement coping with the expansion of their social networks. Additionally, older adults who did not want to burden their social connections during the pandemic (e.g., van Vleet et al, 2022), or had a more isolationist personality, may have been unable or unwilling to form closer relationships with close others. Importantly, younger individuals also struggled with mental health during the pandemic (e.g., Blendermann et al, 2023;Panchal et al, 2021), many of whom were separated from extended family networks (e.g., Loades et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Given age‐related differences in advice‐seeking (Fan, 2021), the solicitation of advice is likely to represent an important avenue for future IGT and ageing research. Conversely, the provision of the advice offered by older adults deserves further attention (see Van Vleet et al., 2022). The final points to consider include that age group differences in deck preference may be clearer when comparing selections from advantageous versus disadvantageous decks.…”
Section: Discussionmentioning
confidence: 99%